COVID-19, public health messaging, and sanitation and hygiene practices in rural India. (21st October 2022) - Pakhtigian, Emily L.; Downs-Tepper, Harlan; Anson, Anisha; Pattanayak, Subhrendu K.
Abstract: Despite the importance of safe sanitation and hygiene for sustainable development and public health, approximately half of India's rural population lacks access to safely managed sanitation. Policies prioritizing improved sanitation access have accelerated coverage, yet barriers to universal access and use remain. In this paper, we investigate how personal experience with a public health shock impacts recall of public health messages and households' sanitation and hygiene practices. Using a panel survey conducted before and after the first wave of the COVID-19 pandemic, and the resulting lockdown, in Bihar, India, we compare public health messaging recall and hygiene and sanitation behaviors among households that experienced severe economic disruptions due to the COVID-19 lockdown and those that did not. We find that households that experienced economic disruptions had a higher recall of public health messaging around safe sanitation and hygiene. In addition, households that experienced these disruptions reported more social distancing, increased handwashing behavior, and reduced open defecation. A major public health shock, the COVID-19 pandemic, increased messaging around the importance of safe hygiene and sanitation for public health in India. We find that personal experience increased the salience of public health messaging, with positive returns to sanitation and hygiene practices. HIGHLIGHTS: The COVID-19 pandemic increased the salience of public health messaging in India. Households impacted economically by COVID-19 increased reported handwashing frequency. Households impacted economically by COVID-19 reduced reported open defecation by 22%. Increasing the salience of public health messaging can lead to safer health behaviors. Graphical Abstract